Creation of dynamic contact network through agent-based simulation - Leow, Guan Hao (2013)
This project is a refinement of a previous Final Year Project, Agent-based Simulation – Canteen (SCE11-0028). It is a canteen environment simulation developed using Crowd Simulation for Military Operations (COSMOS), a framework project for agent-based crowd simulation with agents based on the Recognition Primed Decision (RPD) model. This project also primarily involves generating dynamic contact networks of agents from the simulation, which can be, for example, used to study the spread of diseases in a particular environment.